Toxicological and Repellent Effects of Lantana camara (Verbenaceae) and Eucalyptus citriodora (Myrtaceae) Extracts against Rift Valley Fever Vector, Culex antennatus (Becker) (Diptera: Culicidae) (Journal of Nuclear Technology in Applied Science, 2019)
Culex antennatus (Becker) play an important role in transmission of Rift Valley Fever virus in the Nile Delta of Egypt. The present study aimed to evaluate the larvicidal activity of ethanol 70% and hexane extracts from Lantana camara and Eucalyptus citriodora leaves against the C. antennatus third larval instar. In addition, the repellent activity of the tested extracts against C. antennatus starved females was examined. The obtained results revealed that, hexane extract of tested plants was more effective against 3rd instar larvae of C. antennatus than ethanolic extract. The LC50 values of hexane extracts recorded 84.4, 158.6; 71.3, 129.1 and 64.0, 113.3 ppm after 24, 48 and 72 hours post treatment for L. camara and E. citriodora, respectively. Also, the tested ethanolic and hexane extracts of L. camara and E. citriodora (leaves) evoked a variable degree of repellency against C. antennatus starved females. The ethanolic extract exhibited 86.2, 68.8, 57.9 and 74.1, 59.0, 47.3% protection for L. camara and E. citriodora at 3.33, 1.67 and 0.83 mg/cm2. Potent repellency (92.5%) achieved by L. camara hexane extract at 1.67 mg/cm2 through the 3h post treatment, Also, E. citriodora (leaves) hexane extract showed 88.1, 77.8 and 53.7% repellency at 3.33, 1.67 and 0.83 mg/cm2.
Keywords: Larvicidal; Repellent; Culex antennatus; Lantana camara; Eucalyptus citriodoras